Comparative biological effects of spherical noble metal nanoparticles (Rh, Pd, Ag, Pt, Au) with 4–8 nm diameter - Rostek, Alexander; Breisch, Marina; Pappert, Kevin; Loza, Kateryna; Heggen, Marc; Köller, Manfred; Sengstock, Christina; Epple, Matthias (Beilstein Journal of Nanotechnology, 2018)
For a comparative cytotoxicity study, nanoparticles of the noble metals Rh, Pd, Ag, Pt, and Au (spherical, average diameter 4 to 8 nm) were prepared by reduction in water and colloidally stabilized with poly(N-vinyl pyrrolidone) (PVP). Thus, their shape, size, and surface functionalization were all the same. Size and morphology of the nanoparticles were determined by dynamic light scattering (DLS), analytical disc centrifugation (differential centrifugal sedimentation, DCS), and high-resolution transmission electron microscopy (HRTEM). Cell-biological experiments were performed to determine the effect of particle exposure on the viability of human mesenchymal stem cells (hMSCs). Except for silver, no adverse effect of any of the metal nanoparticles was observed for concentrations up to 50 ppm (50 mg L−1) incubated for 24 h, indicating that noble metal nanoparticles (rhodium, palladium, platinum, gold) that do not release ions are not cytotoxic under these conditions.
Keywords: cytotoxicity; electron microscopy; metals; nanoparticles; nanotoxicity